Optimization of Biodiesel Production from Castor Oil by Transesterification Process - Mohd Mazwil, Nurun Nazahah (Universiti Teknologi PETRONAS, 2014)
The scarcity of fossil fuels, environmental pollution and food crisis are the world’s major issues in current era. Biodiesel is an alternative to fuel, is environmental friendly and biodegradable and can be produced from both edible and non-edible oils. In this work, a non-edible oil, castor oil is used for the production of biodiesel.The biodiesel production is a two-step process, the first step is acid esterification to reduce the free fatty acid (FFA) amount in the oil and the second step is base transesterification to convert the oil completely to biodiesel. Response Surface Methodology is used to optimize the conditions for biodiesel production from castor oil by using a homogeneous catalyst, potassium hydroxide through transesterification process. A quadratic polynomial equation is obtained for biodiesel yield. The studied variables are oil to methanol ratio, catalyst concentration, temperature and time. Results from the optimization are that oil to methanol ratio is 9, 0.5% catalyst, 45oC temperature and 90 minutes. This gives a yield of 83.57% of biodiesel. These parameters is then used for conducting a transesterification process with heterogeneous catalyst, sodium titanate. The results between homogeneous and heterogeneous catalyst is the compared by comparing their density, viscosity and others. The biodiesel’s conversion and its composition are also determined by using the Gas Chromatography Flame Ionization Detector (GC FID) unit.